Sistem Pemprosesan Imej Perubatan - Khalid, Rohaida (Universiti Sains Malaysia, 2005)
Breast cancer is one of the main causes to women death nowadays. Medical specialist uses mammogram and ultrasound screening to detect and identifying the breast tumour. Cervical cancer is second causes to women death. Pap test is used to detect the biological changes of cervical cell. However, sometime medical specialist faces difficulties in analyzing the mammogram, ultrasound and Pap smear images. Medical images, which are analyzed by Radiologist and Patalogist are normally affected by unwanted noise and blur such as blood and sometimes the images are too dark or too bright. These factors contribute to error diagnosis or screening. Therefore, project proposes “Medical Images Processing System” using Borland C++ Builder version 6 to increase the problems. This user-friendly system is developed to improve the weaknessess which occur during the medical images processing. Image processing techniques such as filtering are provided in the system, contrast enhancement, boundary segmentation and edge detection. The results show that the proposed succesfully improved the tumour contrast, segmented the tumour, detected the tumour edges and reduce unwanted noise of the medical images.